Answer:
-1/4
1
-1/4
1
Explanation:
Slope is obtained thus :
(y2 - y1) / (x2 - x1)
Slope ST :
S(1, 4) ; T(5, 3) ;
x1 = 1, y1 = 4 ; x2 = 5 ; y2 = 3
Slope ST = (3 - 4) / (5 - 1) = - 1 / 4
Slope TU :
T(5, 3) ; U(3, 1)
x1 = 5, y1 = 3 ; x2 = 3 ; y2 = 1
Slope TU = (1 - 3) / (3 - 5) = - 2/ - 2 = 1
Slope UV :
U(3, 1) ; V(-1, 2)
x1 = 3, y1 = 1 ; x2 = - 1 ; y2 = 2
Slope UV = (2 - 1) / (-1 - 3) = 1 /-4 = - 1/4
Slope SV:
S(1, 4) ; V(-1, 2)
x1 = 1, y1 = 4 ; x2 = - 1, y2 = 2
Slope SV = (2 - 4) / (-1 - 1) = - 2 / - 2 = 1